Kajian Faktor Keberhasilan Balai Benih Ikan (Bbi) Sukomananti Pada Kegiatan Budidaya Ikan Di Kecamatan Pasaman Kabupaten Pasaman Barat - Siti Aisyah; BS Monica Arfiana; Dicky Rustam; Torang Siahaan (JURNAL PUNDI, 2022)
Increasing the yield of fish seed production is a very important factor in production activities to support the needs of fish farmers in West Pasaman Regency, Seeing the sufficient land area and the number of production ponds, the production of fish seeds should be able to exceed the target but in fact BBI Sukomananti has not been able to produce according to market demand. The purpose of the study was to analyze the factors that influence the success of the Sukamananti Fish Seed Center (BBI) in fish farming activities in Pasaman District, West Pasaman Regency. The method used is a survey method with a research sample of 51 fish cultivators in West Pasaman Regency. The variables used are increased income, fish resources, technology, institutions and policies, social community. Analysis of the data used is multiple linear regression analysis. The success factor of the Sukamananti Fish Seed Center (BBI) on fish cultivation activities in Pasaman District, West Pasaman Regency which has an effect is the fish resource variable, as can be seen from the t test results that t count is greater than t table (4.446 > 1.67793) and the significance level is 0.000 more smaller than 0.05. BBI Sukamananti is considered to have had an impact in quality but is still lacking in terms of quantity because it still does not meet the demands of cultivators in the Pasaman District, West Pasaman Regency, while from the technological, institutional and policy aspects as well as the social influence of the community, it does not have a successful impact on the development of fish farming in the District. Pasaman, West Pasaman Regency.